Glycolipid‐peptide conjugate vaccines elicit CD8+ T‐cell responses and prevent breast cancer metastasis. Issue 7 (3rd July 2022) - Burn, Olivia K; Farrand, Kathryn; Pritchard, Tara; Draper, Sarah; Tang, Ching‐wen; Mooney, Anna H; Schmidt, Alfonso J; Yang, Sung H; Williams, Geoffrey M; Brimble, Margaret A; Kandasamy, Matheswaran; Marshall, Andrew J; et al.
Abstract: Objectives: Metastasis is the principal cause of breast cancer mortality. Vaccines targeting breast cancer antigens have yet to demonstrate clinical efficacy, and there remains an unmet need for safe and effective treatment to reduce the risk of metastasis, particularly for people with triple‐negative breast cancer (TNBC). Certain glycolipids can act as vaccine adjuvants by specifically stimulating natural killer T (NKT) cells to provide a universal form of T‐cell help. Methods: We designed and made a series of conjugate vaccines comprising a prodrug of the NKT cell‐activating glycolipid α‐galactosylceramide covalently linked to tumor‐expressed peptides, and assessed these using E0771‐ and 4T1‐based breast cancer models in vivo . We employed peptides from the model antigen ovalbumin and from clinically relevant breast cancer antigens HER2 and NY‐ESO‐1. Results: Glycolipid‐peptide conjugate vaccines that activate NKT cells led to antigen‐presenting cell activation, induced inflammatory cytokines, and, compared with peptide alone or admixed peptide and α‐galactosylceramide, specifically enhanced CD8 + T‐cell responses against tumor‐associated peptides. Primary tumor growth was delayed by vaccination in all tumor models. Using 4T1‐based cell lines expressing HER2 or NY‐ESO‐1, a single administration of the relevant conjugate vaccine prevented tumor colonisation of the lung following intravenous inoculation of tumor cells or spontaneous metastasis from breast, respectively. Conclusion: Glycolipid‐peptide conjugate vaccines that activate NKT cells prevent lung metastasis in breast cancer models and warrant investigation as adjuvant therapies for high‐risk breast cancer. Abstract : In this study, we found that glycolipid‐peptide conjugate vaccines elicited greater peptide‐specific CD8 + T cell responses than peptide ± GM‐CSF and inhibited breast cancer metastasis to lung.